If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + h = 4 Solving 9 + h = 4 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + h = 4 + -9 Combine like terms: 9 + -9 = 0 0 + h = 4 + -9 h = 4 + -9 Combine like terms: 4 + -9 = -5 h = -5 Simplifying h = -5
| r+15=9+4r+6 | | 45n=22.5 | | 5x+4x=4+8 | | 6x-8=8x-22 | | -15+1=12y+4-11y | | 10(s-5)=-147 | | c=38.54+0.25x | | 8n+5=48 | | 81+49-125+9-32= | | 7x+9=8x+8 | | -3+2=13y-5-12y | | 4x+3x=30+9 | | m/2+5=--3 | | 6(3m-3)=34+5m | | 3x+8=22+x | | 2(1)(6(4)-5)= | | 125*5(3x)=27*27(x) | | 0.35(2y-1)=-0.7y | | d+7=-7 | | y-34+12+3=14 | | 2x+24=.29x | | (x+10)(2x)(2x-30)= | | -2(-3k+4)-7=15 | | -3(x-4)=2(x+1) | | 22.5x-15=12 | | 4n-6=8+2n | | 9=7-2c | | 125*5(3x)=27*27x | | 8x+7=4x+47 | | x+10-18=-5 | | 45+35x=20+40x | | y=2mx+7b |